Perceived threats of infanticide reduce maternal allocation during lactation and lead to elevated oxidative damage in offspring. (12th July 2018) - Gale, Teagan; Garratt, Michael; Brooks, Robert C.
Abstract: Maternal investment is costly to the mother but essential to offspring survival in altrical species. Infanticide by novel males results in loss of maternal investment, and maternal strategies have evolved to mitigate these losses. One such maternal strategy, the Bruce effect, involves spontaneous abortion by females of some mammal species when exposed to a novel male during pregnancy. In mice, the Bruce effect only occurs during early pregnancy, but we have previously found that female mice exposed to a novel male's scent in late pregnancy weaned smaller offspring. Here, we replicate that manipulation to resolve the cause of the reduced weaning weight and subsequent effects on offspring fitness. Females exposed to an unfamiliar male's scent in late pregnancy spent significantly less time nursing their pups during lactation, suggesting that reduced maternal allocation contributes to slower offspring growth. The offspring with a reduced weaning weight exhibited catch‐up growth and reached a normal weight at adulthood. These offspring, however, were found to bear oxidative damage in adulthood, revealing long‐term effects on offspring condition. We conclude that female mice strategically alter their investment in lactation in relation to the likelihood of infanticide, but that this results in long‐term fitness costs to their offspring. A plain language summary is available for this article. Abstract : Plain Language Summary